2008
DOI: 10.2527/jas.2006-807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sex and castration of females on growth performance and carcass and meat quality of heavy pigs destined for the dry-cured industry1

Abstract: Crossbred pigs (n = 240) from Pietrain x Large White sires mated to Landrace x Large White dams, with an average age of 100 d (60.5 +/- 2.3 kg of BW), were used to investigate the effects of sex and slaughter weight (SW) on growth performance and on carcass and meat quality characteristics. There were 6 treatments arranged factorially, with 3 classes (intact females, IF; castrated females, CF; and castrated males, CM) and 2 slaughter weights (114 and 122 kg of BW). Each of the 6 combinations of treatments was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
38
3
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 36 publications
25
38
3
6
Order By: Relevance
“…In fact, carcasses from barrows were fatter than those from gilts (by 30% at the level of 3rd and 4th last ribs and 15% over the GM muscle). These findings agree with other studies on heavy pigs (Latorre et al, 2008;Peinado et al, 2008;Suárez-Belloch et al, 2015a) confirming the high potential for fat deposition of barrows.…”
Section: Carcass Characteristicssupporting
confidence: 93%
See 1 more Smart Citation
“…In fact, carcasses from barrows were fatter than those from gilts (by 30% at the level of 3rd and 4th last ribs and 15% over the GM muscle). These findings agree with other studies on heavy pigs (Latorre et al, 2008;Peinado et al, 2008;Suárez-Belloch et al, 2015a) confirming the high potential for fat deposition of barrows.…”
Section: Carcass Characteristicssupporting
confidence: 93%
“…Regarding the chemical composition, no effect of sex was recorded, although a higher IMF content was expected in LT muscle from barrows than from gilts. In line with the results on carcass fatness and accordance with other authors (Latorre et al, 2008;Peinado et al, 2008), the laboratorial analysis showed higher IMF proportion in pork from barrows but the difference was not significant probably due to the high variability among samples. The sensory benefits of a high IMF content are well known in terms of juiciness and acceptability of meat (Wood et al, 2008).…”
Section: Or Nosupporting
confidence: 90%
“…Afterwards, samples were weighed again and the difference between the weight of the slice before and after conservation in the cooler was divided by the initial weight to determine drip loss. Cooking loss and shear force were determined as described by Honikel (1998) and Peinado et al (2008), respectively.…”
Section: Husbandry and Dietsmentioning
confidence: 99%
“…The samples were vacuum packaged in individual plastic bags and frozen at 2208C during 54 days until subsequent analyses. The FA profile of the samples was determined as described by Peinado et al (2008). Briefly, FA was extracted with diethyl ether from a 200 mg sample and analysed by chromatography (Autosystem XL, Perkin Elmer, Boston, MA, USA).…”
Section: Husbandry and Dietsmentioning
confidence: 99%
See 1 more Smart Citation